تنفيذ تعليم نظم المفردات للمستوى المبتدئ على أساس المدخل السياقي بمدرسة دار الفلاح الدينية رامبان كولون جرمي بندووصا: Implementing Vocabulary System Education for Beginners Based on Contextual Approach at Dar Al-Falah Religious School in Ramban Kulon Cermee Bondowoso - Kholil Imam; Mokhammad Miftakhul Huda; Hind Hussein Obaid (Journal of Arabic Language Teaching, 2024)
The contextual approach focuses on students' interests, experiences, and backgrounds in education. It aims to help students understand and relate learning materials to their daily lives, either personally, socially, or culturally. Research Objectives: (1) To describe the implementation of vocabulary system education for beginners based on the contextual approach at Dar Al-Falah Religious School in Ramban Kulon Cermee Bondowoso. (2) To identify the problems encountered in implementing vocabulary system education for beginners based on the contextual approach at Dar Al-Falah Religious School in Ramban Kulon Cermee Bondowoso. (3) To describe the solutions to the problems encountered in implementing vocabulary system education for beginners based on the contextual approach at Dar Al-Falah Religious School in Ramban Kulon Cermee Bondowoso. Our problem statement and data acquisition methods have been thorough and precise. Through interviews, documentation, and questionnaires, we have gathered data that shows students follow the vocabulary system for beginners in an organized and obedient manner. Furthermore, activities in learning the vocabulary system for beginners run smoothly and are organized, with the enthusiasm and motivation provided by the teacher to the students. This has led to a noticeable increase in students' diligence and enthusiasm in memorizing the vocabulary system for beginners, a promising sign for the effectiveness of our proposed solutions.